Tsunami Vertical Evacuation Building Analysis (Shelter) Based on Number and Location: Case Study of Koto Tangah District- Padang City - Ashar, Faisal; Hadiguna, Rika Ampuh; Faisal, Muhammad (Universitas Negeri Padang, 2024)
Koto Tangah Sub-district is a sub-district where part of its area is located on the coast, making it prone to tsunami disasters. Despite the fact that the large number of exposures in the tsunami red zone predicted to happen in this District, there are only three tsunami shelters in the red zone of Koto Tangah District. The purpose of this study was to determine the distribution of official shelters in Koto Tangah District, the distribution of planned shelters, and the coverage of shelter service areas. The research method used is a quantitative descriptive method. In this study, what is discussed is the number and location of shelters, as well as the location of the planned tsunami shelters. Also, this present study sought to finding out the coverage area that can be served by the shelter with the help of GIS applications. The results of the data analysis are as follows: (1) There are nine villages (kel.) that are in the tsunami red zone of the Koto Tangah District and are not served by official shelters, namely: Kel. Padang Sarai, Kel. Batipuh Panjang, Kel. Lubuk Buaya, Kel. Pasia Nan Tigo, Kel. Batang Kabung Ganting, Kel. Koto Pulai, Kel. Koto Panjang Ikua Koto, Ex. Dadok Stumping Black, and parts of Ex. Parupuk Tabing. (2) The analyzed planned shelters and horizontal points examined that all of the Koto Tangah red zone areas can be served by shelters, and the planned shelters can be reached in the span of 34.5 minutes with a distance of 1554.57 m, meaning that people who are in the tsunami red zone can evacuate safely before the tsunami hits the city. (3) local government needs to add another 6 planned shelters in Kel. Padang Sarai, Kel. Lubuk Buaya, Kel. Pasie Nan Tigo, Kel. Batang Kabung Ganting, and Kel. Parupuk Tabing, with each shelter's planned height of 8.5 meters.